2003
DOI: 10.1093/jee/96.5.1548
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Extent of Resistance to Fipronil in the German Cockroach, Blattella germanica (L.) (Dictyoptera: Blattellidae)

Abstract: Fipronil, a phenylpyrazole insecticide, was made available in 1999 in bait formulations for use against the German cockroach, Blattella germanica (L.). We have investigated resistance to fipronil in the descendants of cockroaches collected just before, or contemporaneously with, the introduction of fipronil baits. Cockroaches were obtained in two types of settings: homes that either had or had not been serviced by a pest management professional while occupied by their current residents. Thorough inspections by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 33 publications
4
25
0
1
Order By: Relevance
“…Our findings are consistent with other studies showing significant indoxacarb (Gondhalekar et al 2013, Ko et al 2016a) and fipronil (Holbrook et al 2003, Chai and Lee 2010, Gondhalekar et al 2011) resistance in German cockroaches. Resistance to indoxacarb and fipronil in the I-IN and D-IL strains are likely the result of prior selection pressure.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are consistent with other studies showing significant indoxacarb (Gondhalekar et al 2013, Ko et al 2016a) and fipronil (Holbrook et al 2003, Chai and Lee 2010, Gondhalekar et al 2011) resistance in German cockroaches. Resistance to indoxacarb and fipronil in the I-IN and D-IL strains are likely the result of prior selection pressure.…”
Section: Discussionsupporting
confidence: 93%
“…Determining the effects of different insecticide deployment strategies on resistance evolution, such as use of single products versus product rotations or mixtures would provide useful information for developing sustainable resistance management strategies for German cockroaches. Even though susceptibility and resistance of field cockroaches against different AIs was observed in our study, effective control of cockroaches might still be achievable by commercially available chemicals because they are highly palatable and contain extremely high insecticide concentrations (Holbrook et al 2003, Gondhalekar and Scharf 2012, Gondhalekar et al 2013, Ko et al 2016a). However, this possibility does not preclude judicial pesticide use to preserve efficacy of presently available pesticide resources (Gondhalekar and Scharf 2013).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…We currently are unable to discern whether the Þpronil resistance in the four strains recorded in this study was due to selection pressure by the Þpronil gel bait, to selection by dieldrin that occurred three decades ago, or both. Holbrook et al (2003) conÞrmed that German cockroach strains that were resistant to cyclodiene were cross-resistant to Þpronil. Kristensen et al (2005) found Þpronil resistance in dieldrin-resistant Danish populations of B. germanica that had never been exposed to Þpronil and demonstrated the involvement of Rdl mutation.…”
Section: Resultsmentioning
confidence: 99%